In vitro study of pinostrobin propionate and pinostrobin butyrate: Cytotoxic activity against breast cancer cell T47D and its selectivity index - Tri Widiandani; Tiffany Tandian; Bagus D. Zufar; Andi Suryadi; Bambang T. Purwanto; Suko Hardjono; Siswandono Siswandono (AOSIS, 2023)
Backgrounds: Pinostrobin has the potential activity as an anti-cancer. However, its activity is still lower than the anticancer drugs on the market. To increase its activity, pinostrobin derivatives have been synthesized, namely pinostrobin propionate and pinostrobin butyrate, which are predicted to have better activity and lower toxicity than pinostrobin after being tested by in silico approach. So the compound deserves to be tested for its anticancer activity and selectivity on normal cells. Objective: This study aims to determine the anticancer activity of pinostrobin propionate and pinostrobin butyrate against the T47D breast cancer cell line and its selectivity against the Vero cell line. Methods: The cytotoxicity test which is anticancer activity test and its selectivity on normal cell were carried out using the MTT(3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay. The cells used were breast cancer cell line T47D and normal Vero cells. The test results were analyzed using a microplate reader with a wavelength of 570 nm. Results: From the analysis of anticancer activity on T47D cells, the IC50 values of pinostrobin, pinostrobin propionate, and pinostrobin butyrate were 2.93, 0.57, and 0.40 mM, respectively. While the results of the cytotoxicity test on Vero cells obtained the CC50 value of pinostrobin, pinostrobin propionate, pinostrobin butyrate was 1.27, 0.94, and 0.89 mM, respectively. So the SI value of pinostrobin (SI=0.4) is smaller than its derivatives (SI=1.7 and 2.2). Meanwhile, pinostrobin butyrate is more selective than pinostrobin propionate. Conclusions: It can be concluded that pinostrobin propionate and pinostrobin butyrate compounds have greater activity and selectivity than pinostrobin so these compounds are promising to be further developed as anticancer candidates.